Does ambiguity matter? Estimating asset pricing models with a multiple-priors recursive utility - Jeong, Daehee; Kim, Hwagyun; Park, Joon Y. (Journal of Financial Economics, 2015)
This paper considers asset pricing models with stochastic differential utility incorporating decision makers׳ concern with ambiguity on true probability measure. Under a representative agent setting, we empirically evaluate alternative preference specifications including a multiple-priors recursive utility. We find that relative risk aversion is estimated around 1–8 with ambiguity aversion and 7.4–15 without ambiguity aversion. Estimated ambiguity aversion is both economically and statistically significant and can explain up to 45% of the average equity premium. The elasticity of intertemporal substitution is higher than one, but its identification appears to be weak, as observed by previous authors.